Design and Building of an Automatic Trash Can Based on Arduino - Astuty, Astuty; Nurfadilah, Anggriani; Annisa, Annisa; Khatima, Khusnul (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
Trash that piles up and exceeds the capacity of the trash bin will create an unhealthy environment and aesthetically look dirty. The lack of use of technological information in waste management by cleaning staff contributes to slow waste handling. This research designs a trash can system that can send information in the form of notifications to officers that the trash can is full and can be controlled via message replies on the Telegram application. This system is designed using an ESP32 microcontroller as a control center, a Sharp Distance infrared sensor to detect the volume of waste in the trash can, an LCD to display the condition of the volume and a DC power window motor to move the container and a Telegram bot as an application that receives notifications and controls the motor. From the results of sensor testing, objects at a distance of >7 cm can activate the motor to work. The network connection when using Indosat IM3 is better than XL-Axiata because the DC motor responds faster to commands. This trash can make it easier for cleaning service to control the condition of the trash can.